Manfaat Pasar Desa Terhadap Masyarakat dan Pendapatan Asli Desa Di Kabupaten Banyuwangi - Jember, Supranoto (JURNAL ADMINISTRASI DAN KEBIJAKAN PUBLIK, 2019)
This study aims to describe the contribution and benefits of village market in Purwoharjo Village, District of Purwoharjo, Banyuwangi Regency. The research applied two analyses, namely analysis of village market contribution and analysis of village market benefits. Analysis of the contribution of village market is related to the real village income, while the analysis of the benefits of village population is in connection with the villagers or the village market users. This research used descriptive qualitative approach, type-4 case study as the research design. The informants were determined by purposive and snowball techniques. The data used were primary data from the research field/location and secondary data from the institution. Data were collected by interview, observation, and documentation. Data validity was examined by extended participation and triangulation. After verification, data were analyzed using interactive model of Miles and Huberman. The research results showed that the contribution of village relate to village real revenue can be seen through IDR value and percentage. From the value of IDR, Purwoharjo Village experienced up or down or fluctuated, while the percentage from 2013-2016 continued to increase. Furthermore, the benefits of village market can be seen in the form of: (a) facilitation for the villagers in meeting their needs; (b) market usage for place of work; (c) labor absorption; (d) Attraction to investors from outside of the village; and (e) villagers’ opportunity to sell their agricultural products at the village market.